Horizontal winds derived from the polar mesospheric cloud images as observed by the CIPS instrument on the AIM satellite. Issue 11 (5th June 2015) - Rong, P. P.; Yue, J.; Russell, J. M.; Lumpe, J. D.; Gong, J.; Wu, D. L.; Randall, C. E.
Abstract: A cloud pattern matching technique is applied to polar mesospheric cloud (PMC) images taken by the Cloud Imaging and Particle Size instrument (CIPS) to infer the wind velocities in the mesopause region. CIPS measurements are analyzed to detect patterns that repeat from one orbit to the next but are displaced in location; the displacement provides a measure of the wind velocity. Pattern matching is achieved by resampling the CIPS data to longitude and latitude grids with the grid‐box size forced at ~5 km in both directions. The correlated patterns are searched within a geographic region referred to as a "frame" of ~500 km in longitude × 400 km in latitude. The histograms of the derived velocities indicate that easterly winds prevail, with a mean zonal wind of −20 to −15 m/s. Mean meridional winds are overall small, but in late summer the histogram indicated a poleward wind of ~20–30 m/s. The variability of CIPS cloud albedo on consecutive orbits is also examined at fixed geolocations. The statistical results suggest that ~86% of pairs underwent mean cloud albedo variation of < 50% on consecutive orbits, suggesting a moderate change. It is also found that the correlation of the cloud structures between two consecutive orbits at a fixed location is generally poor. These findings suggest that cloud patterns are subject to wind advection, but the cloud patches are more extended in size than the movement that occurs. Cloud voids are found to be more likely to remain at the same geolocations. Key Points: Cloud pattern matching technique is applied to polar mesospheric clouds Derived velocities indicate prevailing easterly winds of 30–70 m/s Prevailing meridional winds are zero in July but are poleward in August